2014
DOI: 10.1016/j.bpj.2014.05.031
|View full text |Cite
|
Sign up to set email alerts
|

A Modular View of the Diversity of Cell-Density-Encoding Schemes in Bacterial Quorum-Sensing Systems

Abstract: Certain environmental parameters are accessible to cells only indirectly and require an encoding step for cells to retrieve the relevant information. A prominent example is the phenomenon of quorum sensing by microorganisms, where information about cell density is encoded by means of secreted signaling molecules. The mapping of cell density to signal molecule concentration and the corresponding network modules involved have been at least partially characterized in many bacteria, and vary markedly between diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…We refer to the function R( p ) as the response function, which is the same for all individuals. The response function encapsulates all biochemical steps involved in the autoinducer production between perception of the average production level p and adjustment of the individual production degree to R( p ) in response [2,11,35,46,47]; see Fig. 1(B).…”
Section: Set-up Of the Quorum-sensing Modelmentioning
confidence: 99%
“…We refer to the function R( p ) as the response function, which is the same for all individuals. The response function encapsulates all biochemical steps involved in the autoinducer production between perception of the average production level p and adjustment of the individual production degree to R( p ) in response [2,11,35,46,47]; see Fig. 1(B).…”
Section: Set-up Of the Quorum-sensing Modelmentioning
confidence: 99%
“…Indeed, bacterial species have evolved independently to have differential contributions from multiple signaling inputs to control particular behaviors, which depend on specific environmental niches (e.g., in V. cholerae , biofilm formation in the aquatic environment and virulence factor production inside the host, both of which are controlled by QS). V. cholerae is just one of several QS bacterial species that utilizes a multi-signal network configuration to accomplish specific goals (Cornforth, et al 2014, Drees, et al 2014). Other research has shown that there is an association between variable environmental challenges and multi-signal complexity for bacteria that have multiple niches, like V. cholerae , Pseudomonas aeruginosa , Burkholderia thailandensis , and some Bacillus species which have niches both inside and outside of human hosts (Cornforth, et al 2014, Pollak, et al 2015, Schuster, et al 2013, Williams, et al 2007, Yang and Lan 2015).…”
Section: Bacteria Are Multilingual To Adapt To Their Changing Surrounmentioning
confidence: 99%
“…This phenomenon was first described for luminescent bacteria such as the symbiotic marine bacterium Vibrio fischeri (1)(2)(3). Since then, many different QS systems have been discovered in Gram-negative as well as Gram-positive bacteria (4). AIs are synthesized and released into the environment, therefore accumulating in a cell-number-dependent manner.…”
mentioning
confidence: 99%